2017
DOI: 10.5430/ijba.v8n2p47
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management in Mexican Manufacturing Small Business

Abstract: In an unpredictable business environment, such as the one that characterized the economy at the beginning of the 21 st century, knowledge management has become one of the most valued intangible assets by organizations that have recognized the importance of knowledge in the creation and development of competitive advantages and performance. However, most investigations have been focused on big enterprises, only a few have been paid attention to small and medium-sized enterprises (SMEs). For this reason, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Service researchers should be interested in understanding the service challenges of new ventures because a significant body of research in entrepreneurship has shown that new ventures not only represent a distinct firm life-cycle stage but more importantly face distinct strategic and tactical challenges (Covin and Slevin 1989; Robinson et al 1984). The findings complement the servitization literature by providing an understanding of the role of service intensity at an early organizational life-cycle stage beyond the established firms, and small- and medium-sized enterprises (SMEs) studied in the servitization literature (Ambroise, Prim-Allaz, and Teyssier 2018; Ha, Lee, and Kim 2016; Maldonado-Guzman, Marin-Aguilar, and Pinzon-Castro 2017; Valtakoski and Witell 2018).…”
Section: Introductionmentioning
confidence: 67%
“…Service researchers should be interested in understanding the service challenges of new ventures because a significant body of research in entrepreneurship has shown that new ventures not only represent a distinct firm life-cycle stage but more importantly face distinct strategic and tactical challenges (Covin and Slevin 1989; Robinson et al 1984). The findings complement the servitization literature by providing an understanding of the role of service intensity at an early organizational life-cycle stage beyond the established firms, and small- and medium-sized enterprises (SMEs) studied in the servitization literature (Ambroise, Prim-Allaz, and Teyssier 2018; Ha, Lee, and Kim 2016; Maldonado-Guzman, Marin-Aguilar, and Pinzon-Castro 2017; Valtakoski and Witell 2018).…”
Section: Introductionmentioning
confidence: 67%